2021
DOI: 10.1186/s40545-021-00392-x
|View full text |Cite
|
Sign up to set email alerts
|

Expectations and experiences of women regarding maternal healthcare services in Pakistan: challenges and lessons to be learnt

Abstract: Background Access to maternal healthcare services is an essential pre-requisite for improving women’s health. However, due to poor access and underutilization, women in developing countries remain vulnerable to various complications. Evaluation of quality maternal healthcare services in any country must include the opinions of the women being as a key stakeholder utilizing maternal healthcare services. Aim The present study was designed to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Anticipatory guidance, which prepares mothers for the process of delivery and labor, guides them about breastfeeding practices, and creates awareness about the significance of light exercise and nutrition, etc., was also not considered of good quality by the users. Similar findings were reported in a qualitative study done in twin cities of Pakistan during the pandemic [ 38 ]. Another qualitative study done in Pakistan during the pandemic disclosed that it was difficult to find doctors, nurses, or health centers that could provide the necessary services during that period.…”
Section: Discussionsupporting
confidence: 90%
“…Anticipatory guidance, which prepares mothers for the process of delivery and labor, guides them about breastfeeding practices, and creates awareness about the significance of light exercise and nutrition, etc., was also not considered of good quality by the users. Similar findings were reported in a qualitative study done in twin cities of Pakistan during the pandemic [ 38 ]. Another qualitative study done in Pakistan during the pandemic disclosed that it was difficult to find doctors, nurses, or health centers that could provide the necessary services during that period.…”
Section: Discussionsupporting
confidence: 90%
“…While a minority (23%) of new mothers worried about not being able to breastfeed [30] , most mothers (50% to 94%) breastfed during their hospital stay [37] , [38] , [52] , [62] , [85] of which 48.3% to 89.3% reported receiving adequate breastfeeding support. Furthermore, a comparison of breastfeeding rates between COVID positive mothers and COVID negative mothers showed no difference between groups [39] , [73] , with 57% [81] to 69% [46] of COVID positive mothers doing direct breastfeeding during their hospital stay. However, qualitative findings revealed that mothers who were unable to get in-person breastfeeding support or had virtual lactation consultation instead reported more difficulty in breastfeeding [44] , [50] , [57] , [75] , [78] with some resorting to a change to formula feeding [43] , [45] .…”
Section: Resultsmentioning
confidence: 89%
“…More than half the mothers (51.8% to 55.1%) in McMillan [64] , Sanders and Blaylock [41] and Burgess [51] studies reported a change to virtual antenatal visits or telephone or video calls. Some mothers praised virtual consultations and telemedicine as time-saving, efficient, and providing access to healthcare professionals [40] , [56] , [59] , [73] . Although 61.4% of mothers in Burgess’ study [51] were satisfied with virtual care and 86% reported adequate antenatal care, 93.2% still preferred face-to-face classes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations